F‐Actin Polarization and Microtubule Integrity Direct Regeneration Patterns and Polarity of Cell Outgrowth in Wound‐Induced Reprogramming - Huang, Yi‐Ting; Yen, Yun‐Ching; Vermeer, Joop E. M.; Willemsen, Viola; Tang, Han (Plant, cell and environment, 2025)
Plants have developed a high regenerative capacity to repair damaged tissues and regenerate new organs in response to injury. When wounded, cells detect mechanical forces through their cytoskeletons and transmit molecular signals to the nucleus, triggering cell reprogramming. As mechanosensing and cell reprogramming have been studied separately, the connection between these processes and the role of cytoskeletal networks in regeneration is still unclear. This study used Physcomitrium patens to investigate the spatiotemporal dynamics of actin filaments and microtubules during wound‐induced cell reprogramming. Upon laser‐induced wounding, we observed a rapid and localized accumulation of F‐actin at the plasma membrane of the neighboring cells next to the wounding site, whereas microtubules showed no immediate discernible changes. Disruption of F‐actin severely impaired overall regeneration, leading to significant reductions in the reprogramming rate. Perturbations of microtubules primarily impacted regenerative cell divisions. Depolymerization of cytoskeletal networks altered regeneration patterns, reflected in the higher ratio of cell outgrowth to division and the outgrowth polarity. These findings underscore the functional role of the cytoskeleton in regulating cell reprogramming. This study reveals that early cytoskeletal polarization after wounding guides the polarity of cell outgrowth, providing new insights into how plants regenerate from mechanical damage. This study establishes a precise wounding system in Physcomitrium patens leaves, enabling cellular‐level analysis of regeneration. We show that rapid F‐actin polarization and sustained microtubule integrity are both essential for guiding cell polarity and proper regeneration patterns.